2014
DOI: 10.2214/ajr.13.11408
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of a Mobile Digital Specimen Radiography System for Intraoperative Specimen Verification

Abstract: Mobile digital specimen radiography allows high diagnostic confidence for verification of target excision in breast specimens across target types, despite lower image quality. Substituting this modality for conventional digital mammography can eliminate delays associated with specimen transport, potentially decreasing surgical duration and increasing operating room throughput.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Kaufman et al 3 reported DSR and IDSM to be equally accurate in relation to identification of the target lesion by either surgeon or radiologist. IDSM has been shown to be more accurate for invasive than in situ disease, 6 to identify the index lesion, in 97% of patients 7 and to be reliable in identifying clear margins. 8 We identified 100% of lesions on specimen radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Kaufman et al 3 reported DSR and IDSM to be equally accurate in relation to identification of the target lesion by either surgeon or radiologist. IDSM has been shown to be more accurate for invasive than in situ disease, 6 to identify the index lesion, in 97% of patients 7 and to be reliable in identifying clear margins. 8 We identified 100% of lesions on specimen radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…This shortens the duration of anaesthesia, reducing morbidity and mortality, and decreases operating room occupancy, thus reducing costs, while still providing comparable results to digital mammography. [14][15][16] The aim of this study was to directly compare the diagnostic performance of full-field digital mammography (FFDM), digital breast tomosynthesis and a dedicated digital specimen radiography system (SRS) for the evaluation of resected breast lesions in consecutive patients, and to compare the margin status of resected lesions versus the final pathological report.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 To save time during surgery, the use of portable intraoperative X-ray systems to take images of the removed tissue inside the operating room is becoming popular. [8][9][10][11] These X-ray systems are based on a filament, the cathode, which is heated to emit electrons by thermionic emission. The emitted electron beam is targeted to a reflection-type metal, the anode, which generates an Xray beam in the direction perpendicular to the direction of the electron beam.…”
Section: Introductionmentioning
confidence: 99%